Overview of Weight Gain in Babies Aged 3-6 Months Who have Been Exclusively Breastfeeded Since Birth - Ardirefi Muhammad Fadhil; Rahmini Shabariah; Meita Dwi Utami; Fita Ferdiana; Tri Ariguntar Wikanningtyas; Farsida Farsida (Indonesian Journal of Global Health Research, 2026)
Exclusive breastfeeding is the gold standard for providing nutrition for newborns up to the first six months of life. The World Health Organization (WHO) and the Indonesian Pediatrician Association (IDAI) recommend exclusive breastfeeding because it provides significant benefits for babies growth, development, and health, including optimal weight gain. In Indonesia, the coverage of exclusive breastfeeding has not yet reached the national target (80%), despite extensive breastfeeding promotion programs. This study aimed to determine the weight gain of babies aged 3-6 months who were exclusively breastfed from birth. This descriptive cross-sectional study was conducted in December 2024 at the Kramat Jati Community Health Center, East Jakarta. The study included 30 babies aged 3–6 months who were exclusively breastfed from birth, selected using a total sampling technique. Data were collected through interviews with mothers, anthropometric measurements of infant weight and length, and medical records. Univariate analysis was performed to describe the distribution of study variables. The results showed that most babies experienced weight gain in accordance with WHO growth standards. The average weight gain of babies aged 3-6 months who were exclusively breastfed was within the normal range.